Has Austria's Accession to the EU Triggered an Increase in Competition? A Sectoral Markup Study - Harald Badinger; Fritz Breuss (Austrian Institute of Economic Research (WIFO), 2004)
We estimate the pro-competitive effects of Austria's participation in the Single Market after its EU accession in 1995 in terms of firms' market power as measured by the Lerner index, using a sample of 46 industries and 7 industry groups, covering the period 1978 to 2001. In the framework of the markup estimation method suggested by Roeger (1995), we test for both an instantaneous structural break between 1993 and 1998 and also estimate logistic smooth transition models to take up the proposition that the regime shift is likely to have occurred (to be occurring) gradually rather than as a big bang. In sum the results provide no reason for being euphoric: pronounced markup reductions were only found in three industry groups (mining and quarrying, wholesale and retail trade; financial services and real estate). At the more disaggregate level, the picture is mixed: both increases and reductions in market power were found.
Keywords: L11; F15; 330; EU; markup; market power; Single Market; EU-Binnenmarkt; Mitgliedschaft; Branchenentwicklung; Marktmacht; Schätzung; Österreich; Wirkungsanalyse